Platelet-to-C-reactive protein ratio stratifies surgical risk and mortality in necrotizing enterocolitis neonates with portal venous gas - Zhang, Xinyin; Wei, Huan; Tan, Qi; Wang, Zhengli; Guo, Zhenhua; Liu, Wei; Cao, Jian (Frontiers in Pediatrics, 2026)
BackgroundPortal venous gas (PVG) represents a severe complication of necrotizing enterocolitis (NEC), typically signaling disease progression and a poor prognosis. While PVG has traditionally been regarded as an indication for surgical intervention in NEC, accumulating clinical evidence indicates that not all cases require operative management. Currently, surgical decision-making for NEC neonates with PVG primarily relies on subjective clinical assessments by physicians, resulting in substantial management uncertainty. The platelet-to-C-reactive protein ratio (PCR), an objective and convenient biomarker integrating information on disseminated intravascular coagulation and systemic inflammation, has demonstrated predictive value in neonatal sepsis and other conditions. However, the utility of the PCR has not yet been explored in NEC-PVG patients. This study retrospectively evaluates the predictive value of the PCR for surgical intervention and prognosis in this high-risk population, aiming to facilitate early identification and improve clinical outcomes.MethodsThis retrospective single-center cohort study analyzed 186 neonates diagnosed with NEC (Bell stage ≥ IIa) and ultrasonographically confirmed PVG (2021–2024). We evaluated the PCR, calculated at the time of PVG diagnosis, for predicting surgical intervention and 30-day mortality by employing multivariate logistic regression (which included collinearity assessment and bootstrap validation) to identify independent factors and receiver operating characteristic (ROC) analysis to assess predictive performance and determine optimal cutoff values, supplemented by sensitivity analyses.ResultsThe cohort demonstrated a surgical intervention rate of 37.10% (69/186) and a 30-day mortality of 13.98% (26/186). Multivariate analysis identified the PCR as an independent predictor for both surgical intervention (adjusted odds ratio (aOR) = 0.77, 95% CI: 0.69–0.86) and mortality (aOR = 0.80, 95% CI: 0.69–0.92). ROC curve analysis established PCR thresholds of ≤4.84 × 109/mg for surgical intervention (AUC 0.84; sensitivity 80%, specificity 85%) and ≤2.57 × 109/mg for mortality prediction (AUC 0.80; sensitivity 69%, specificity 91%).ConclusionsThis study suggests that the PCR is a promising predictor of surgical intervention and mortality risk in NEC-PVG patients, demonstrating superior predictive performance compared to individual parameters. Based on these findings, we propose the incorporation of PCR testing into standard clinical monitoring protocols, using 4.84 × 109/mg as a potential cutoff value to inform therapeutic decision-making. This approach may improve the clinical management and outcomes in this high-risk population.